Contribution of Ibn Omer Island Scholars to Islamic Sciences during the 5-10 AH/11-16CE Centuries - Suleiman, Hakim Ramadan; Al-Manshdawi, خضير (Humanities Journal of University of Zakho, 2022)
The summary The study of the Euphrates Island region is one of the studies worthy of attention due to its political, economic, and scientific importance, as well as its active role in the events of Islamic history. The Euphrates Island has attracted the attention of many Arab and Muslim historians, countrymen, and a group of orientalists due to the importance of Ibn Omar Island in being an important part of the Euphrates Island and in being one of the areas with a Kurdish majority, where the Kurds had a distinguished role in the political, economic and administrative aspects as well as their civilized role on that island and their outstanding scientific contributions, religious sciences come at the forefront, they added to Islamic civilization which I took as the subject of my research. The research is divided into three sections: in the first of which I talked about the location, geography and naming of the island of Ibn Omar and the scholars who were affiliated with; the second section tackles the scholars of the Holy Qur’an in the island of Ibn Omar; while the last topic was devoted to scholars of hadith and jurisprudence. It has become clear to us through this research that most of the scholars of Ibn Umar Island in the religious sciences are from the Kurds who had a prominent role in the study and teaching of these sciences, and that the Ibn Umar Island was an important center of the teaching centers of religious sciences. The evidence for this is the influx of many scholars of The Holy Qur’an and Hadith to teach these sciences on the island, as well as the flock of students of science from the various Islamic regions to the island of Ibn Umar to study these sciences.